Symposium 5: Ideas of Community and Implications for Theorising Networked Learning - Hodgson, Vivien; Fox, Steve; Reynolds, Michael; Perriton, Linda; Reedy, Patrick (Proceedings of the International Conference on Networked Learning, 2002)
The aim of the proposed symposium is to look at the different ways that the idea of community is being used inside and outside of the educational literature. The intention is to look at a wider literature than that which is most regularly referred to within the education and learning literature. The proposed papers will attempt to use the ideas within these different literatures to examine and critique both the potential and/or imagined benefits and issues that are assumed or claimed for the idea of community within leaning situations, within educational contexts and within networked learning in particular. During the symposium we will seek to draw on both theoretical as well as practical work that draws on and develops the idea of community. We hope that the symposium will make a contribution to the development of both the theory and practise of networked leaning. Papers: Networks and Communities: an Actor-Network Critique of Ideas on Community and Implications for Networked Learning Steve Fox Network Learning and Ideas of Community Vivien Hodgson and Michael Reynolds Walk on by: anarchist possibilities for the reconceptualisation of the virtual community Linda Perriton and Patrick Reedy